Membangun Komitmen Kuat : Peran Kompetensi & Budaya pada CV. Taman Agrowisata Bukit Naang - Husein Husein; Librina Tria Putri; Abshor Marantika (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study focuses on efforts to build strong organizational commitment through the roles of competence and organizational culture at CV. Taman Agrowisata Bukit Naang Bangkinang. Organizational commitment is considered a reflection of individual loyalty and attachment to the organization, manifested through a strong belief in the organization’s values and goals, the willingness to work towards the organization's benefit, and the desire to remain a part of it. This research utilized a quantitative approach, specifically multiple regression analysis, to assess the impact of competence and organizational culture on organizational commitment. A total of 38 respondents were selected using a census method. Hypothesis testing was performed through t-tests and F-tests to examine the partial and simultaneous effects of the independent variables on the dependent variable. The study found that both competence and organizational culture significantly influence organizational commitment, both in isolation and when considered together. The analysis showed a strong positive relationship between competence, organizational culture, and organizational commitment, with the independent variables explaining 78.50% of the variance in organizational commitment. These results indicate that improving employee competence and strengthening the organizational culture are vital strategies for fostering long-term commitment within the company. Additionally, the study highlights the importance of aligning organizational culture with the values and goals of the organization to enhance overall employee engagement. By focusing on these areas, CV. Taman Agrowisata Bukit Naang can cultivate a committed workforce, which is essential for sustaining high levels of performance and organizational success. This research contributes to a better understanding of the factors that drive organizational commitment and provides practical recommendations for companies aiming to strengthen their workforce's loyalty and engagement in today’s competitive business environment.